Muriel Gardiner papers - Gardiner, Muriel, 1901-1985.; Pankejeff, Sergius, 1887-1979.
Correspondence, writings, research material, publishing material, photographs, slides, and other papers pertaining to Gardiner's acquaintance with Sergius Pankejeff, the "Wolf-Man" of Freudian analysis. Gardiner was Pankejeff's analyst for many years and was the editor of his autobiography, The Wolf-Man (1971). Includes draft fragments of the autobiography and other writings by Gardiner, Pankejeff, and others. Correspondents include Felix Augenfeld, K.R. Eissler, Anna Freud, Ernest Jones, Sergius Pankejeff, and Stephen Spender.
Psychoanalyst and author.
Collection material in English, German, and French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Augenfeld, Felix, -- 1893-1984 -- Correspondence; Eissler, K. R. -- 1908-1999 -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Jones, Ernest, -- 1879-1958 -- Correspondence; Pankejeff, Sergius, -- 1887-1979.; Pankejeff, Sergius, -- 1887-1979 -- Correspondence; Spender, Stephen, -- 1909-1995 -- Correspondence; Psychoanalysis -- Case studies; Authors; Psychoanalysts